Aplikasi Location Based Service (LBS) Untuk Informasi Dan Pencarian Lokasi Rumah Makan Halal Di Kota Kupang Berbasis Android - Nisa Aulia; Patrisius Batarius; Yovinia Carmeneja Hoar Siki (Paradigma, 2020)
Kupang City is a municipality and also the capital of East Nusa Tenggara Province. Various types of ethnicity, race, religion exist in the city of Kupang. The type of food and tastes also vary according to the race character in Kupang City. It is often a separate issue fore some migrant communities, especially for Muslim communities who visit Kupang City when looking for Halal Restaurants. For Muslim communities who want to find the location of the nearest Halal Restaurant in the city of Kupang they will usually ask the people around and browse the streets, but this will certainly take a long time. Therefore we need an Android-based Location Based Service (LBS) application that can provide clear information about the location of Halal Restaurants in the city of Kupang. In this study the system development method used is the Rational Unified Process (RUP) method. This application was built using the Java programming language and Kotlin, SQLite as a database. This research resulted in an Android-based Location Based Service application that provides services in the form of clear location information such as coordinates and distance to halal restaurants in Kupang City.